Usborne Illustrated Fairy Tales - Sarah Courtauld (London, United Kingdom Usborne Publishing Ltd, 2017)
A fantastic treasury of stories guaranteed to delight and entertain young children. Includes ten classic fairytales by authors such as the Brothers Grimm and Hans Christian Andersen, including The Frog Prince, Little Red Riding Hood and The Swan Princess. All stories feature charming and vivid illustrations. A gorgeous giftbook with an attractive hardback cover and a ribbon marker.
Keywords: Traditional Literature - Fairytales -- Traditional Literature - Fairytales